(3bUGFO UhajIs - (3YHO GdZfj Hf ESeGYjd Hf YHO GdZfj GdfGHdSj,J (B1143 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eNJQY GdhLhO CeG HYO ajbhd GdYHO GdabjQ YHO GdZfi GdfGHdSi gPg fSeGJ CfSjI hfaMGJ bOSjI CKeQJ HgG QjGV GdbdhH hdeYJ efgG HhGQb GdMbGFb s
(3BNQgG (B:s
(3hbGd CjVkG ehGdjkG cd GdcdGe cdGec jGYXje GdTCf EeG HhMi gh GdEdgGe ddEfSGf Ch ef hQGA MLGH UhQI GdCchGf Ch JQSd GdeQSd HGdJHdjZ hGdJHjGf Je s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdhWfjI s
Keywords: (3GdJUha hGdBOGH GdTQYjIs